THREE DIMENSIONAL MULTI TARGET DIRECTIONAL DRILLING DESIGN - RISMANTO (NIM : 12299039), RIZAL
Multi target drilling is defined as a drilling operation to penetrate a well which has more than one productive zone. Directional drilling techniques is used in this operation, considering that the productive zones do not always reside in precisely below the drilling site. In this paper, the principal of the design is the simplification of the three dimensional problem into two dimensional. Well bore trajectory model is created by plotting TVD versus North curve and North versus East curve. Bezier Curve method is used in plotting the curves in order to get a smooth trajectory. The Balanced Tangential method is applied for validation of the calculation result. These results will be compared to find the error. TVD, North, East, and Direction of each target are the parameters compared. Sensitivity test is conducted by changing the depth interval that is used in the calculation. The results of sensitivity test show that the smaller depth interval will give lower error. The results also indicate that 10 ft interval will give good calculation result with errors for all parameters maintained below 1 %.